Rancang Bangun Sistem Informasi Lembaga Sertifikasi Profesi Universitas Bung Hatta Berbasis Web - Dony Novaliendry; Afiful Azkia (Universitas Negeri Padang, 2021)
Professional certification is an effort to recognize a person's competence by the required work competency standards. Bung Hatta University Professional Certification Institute (LSP) is an agency implementing competency certification activities that have received a license from the National Professional Certification Agency (BNSP) to certify students from various fields of science and professions at Bung Hatta University. Bung Hatta University LSP has the status of the first party LSP educational institutions. The registration process for certification at the Bung Hatta University LSP is still done manually by filling in several paper forms. This is considered ineffective considering the current technological advances. By developing a website-based information system, this can be overcome. The purpose of designing a website-based information system is to produce an information system that can assist the certification process and can be accessed by any relevant user anytime and anywhere. This information system was developed using the waterfall method. This method has several stages, namely the needs analysis, design, implementation, and testing stage. The design of this information system used Unified Modeling Language (UML) and implemented using the Yii2 framework as a PHP framework and MySQL as a Database Management System (DBMS). The design of this information system resulted in a web-based Information System for Bung Hatta University LSP, which focused on the initial administrative process.